Certainty, trust and evidence: Towards an integrative model of confidence in multi-agent systems - Basheer G.S.; Ahmad M.S.; Tang A.Y.C.; Graf S. (Elsevier Ltd, 2023)
Decision making; Certainty; Confidence; Decision making process; Evidence-based; Heterogeneous agents; Integrative modeling; Local confidence; Trust; Multi agent systems